2008
DOI: 10.1158/0008-5472.can-07-6769
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase Inhibition Broadly Sensitizes Glioblastoma Cells to Death Receptor– and Drug-Induced Apoptosis

Abstract: The aberrant activity of the phosphatidylinositol 3-kinase (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
120
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 46 publications
13
120
0
1
Order By: Relevance
“…Furthermore, we previously showed that inhibition of PI3K sensitizes GBM to chemotherapy-and to death receptor-induced apoptosis (Opel et al, 2008). A similar importance of the PI3K/Akt pathway has also been reported in ovarian, gastric, breast and lung cancer (Jiang and Liu, 2008), as well as in neuroblastoma, for which it was recently shown that aberrant activation of Akt correlates with reduced life expectancy (Opel et al, 2007).…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Furthermore, we previously showed that inhibition of PI3K sensitizes GBM to chemotherapy-and to death receptor-induced apoptosis (Opel et al, 2008). A similar importance of the PI3K/Akt pathway has also been reported in ovarian, gastric, breast and lung cancer (Jiang and Liu, 2008), as well as in neuroblastoma, for which it was recently shown that aberrant activation of Akt correlates with reduced life expectancy (Opel et al, 2007).…”
Section: Introductionsupporting
confidence: 57%
“…This might also explain in part the reduced sensitization effect of PI-103 when combined with temozolomide, which is an alkylating agent (Tisdale, 1985) and damages DNA by generating O 6 -alkylguanine, which is repaired primarily independent of DNA-PK (Christmann et al, 2003). Indeed, inhibition of PI3K-mediated signaling also enhances apoptosis sensitivity in GBM cells in an NHEJ-independent manner, as we have previously shown for agents that do not primarily cause DNA damage, that is, death receptor ligands such as TRAIL and anti-CD95 agonistic antibody (Opel et al, 2008). Intriguingly, in line with recent observations regarding the pharmacokinetics of inhibitor-induced cancer cell death (Shah et al, 2008), we also found that a brief, but potent inhibition of PI3K administered concurrently with a DNA-damaging drug is sufficient to commit GBM cells to apoptosis and to suppress clonogenic growth.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations